Significant Resolution of Female Sexual Dysfunction after Bariatric Surgery - Bond, Dale S. (2010)
BACKGROUND: We previously reported that the majority of women seeking bariatric surgery had female sexual dysfunction (FSD) as defined by the validated Female Sexual Function Index (FSFI). OBJECTIVE: The current study examined whether FSD resolves after bariatric surgery. SETTING: The Miriam Hospital, Providence RI, USA. METHODS: Fifty-four reportedly sexually active women (43.3±9.5 years) completed the FSFI pre- and 6-months post-operatively after a mean excess weight loss (%EWL) of 42.3% [Laparoscopic adjustable gastric banding (LAGB) n=38; %EWL=34.6±15.7; Roux-en-Y gastric bypass (RYGB) n=16; %EWL=60.0±21.2). The FSFI assesses sexual function across six domains with higher scores indicating better sexual function. Summing of these scores yields a FSFI-total score (range=2–36 with ≤26.55=FSD). RESULTS: Before surgery, 34 women (63%) had scores indicative of FSD. By 6-months after surgery, FSD had resolved in 23 of these 34 (68%) women, and only 1 woman developed FSD. In the entire sample, there were significant (p<0.05) improvements from pre- to post-surgery on all FSFI domains. FSFI-total scores improved after LAGB (24.2±5.9 to 29.1±4.1, p<0.001) and RYGB (23.7±7.7 to 30.0±4.7, p<0.001). In regression analyses, being married, younger age, and worse preoperative sexual function were related to greater sexual function improvements. Postoperatively, participants’ FSFI-total scores were indistinguishable from published normative controls (29.4±4.3 vs. 30.5±5.3, p=0.18). CONCLUSION: FSD resolved in a large percentage of women. Sexual functioning in the entire sample improved to levels consistent with normative controls. This improvement in sexual function did not depend on surgery type or weight loss amount, and appears to be an additional benefit for women undergoing bariatric surgery.